Juvenile specimen of Megaraptor (Dinosauria, Theropoda) sheds light about tyrannosauroid radiation - Porfiri, Juan D. (2014)
Megaraptorids are a group of predatory dinosaurs that inhabited Gondwana from Cenomanian to Santonian times (Late Cretaceous). Phylogenetic relationships of megaraptorids have been matter of recent debate, being alternatively interpreted as basal coelurosaurs, carcharodontosaurian allosauroids, megalosauroids, and basal tyrannosauroids. One of the main reasons for such different interpretations is the incomplete nature of most available megaraptorid skeletons and, in particular, the scarce information about their cranial anatomy. Here we describe a partially preserved skeleton of a juvenile specimen of Megaraptor namunhuaiquii that provides substantial new information about the cranial morphology of this Patagonian taxon. The specimen comes from the Upper Cretaceous (Turonian–Coniacian) of the Portezuelo Formation, northwestern Patagonia, Argentina. The anatomy of the new specimen bolsters the recently proposed hypothesis that megaraptorids are nested within Coelurosauria, and possibly within Tyrannosauroidea. The most relevant features that megaraptorans share with tyrannosauroids include several foramina on the premaxillary body, extremely long and straight prenarial process of the premaxilla, incisiviform premaxillary teeth with a D-shaped cross-section, and cranially expanded supratemporal fossae separated from each other by a sharp sagittal median crest on frontals, which was presumably extended caudally above the parietals (not preserved). Information gathered from the present specimen allows to make for the first time a reconstruction of the skull of Megaraptor and hypothesize about evolutionary trends within Tyrannosauroidea.